Perceived legitimacy of intergroup status differences: its prediction by relative ingroup prototypicality - Weber, U.; Mummendey, A.; Waldzus, S. (European Journal Of Social Psychology, 2002)
Research demonstrates that the perceived legitimacy of intergroup status differences has profound effects on intergroup attitudes, emotions and behavior. However, there has only been little intergroup research that predicts the perception of legitimacy. We hypothesize that the perception of legitimate or illegitime status relations depends upon the perceived relative prototypicality of the ingroup for the inclusive category. Since the prototype of the inclusive category provides a normative comparison standard for subgroup evaluation, similarity to this standard (i.e. prototypicality) should be positively evaluated and used to justify high status. A first study in a natural intergroup context (N?=?67) offered correlational data in support of the predicted relationship. The second study (N?=?60), using Germans as ingroup with Poles as outgroup and Europe as inclusive category, demonstrated that the link between prototypicality and legitimacy is contingent upon the valence of the inclusive category. In order to elucidate the causal direction, the third study manipulated relative prototypicality in an artificial intergroup context (N?=?94) and introduced status as a moderator variable. Overall, we found strong support for the hypothesis that legitimacy is related to prototypicality and that this relation is moderated by ingroup status and valence of the inclusive category.